Comparison of capture and escape rates between different types of portable cowbird traps - Mary Anne McLeod; Thomas J. Koronkiewicz (Wildlife Society Bulletin)
ABSTRACT Control of brown‐headed cowbirds (Molothrus ater) is often advocated to reduce parasitism and improve nesting success of sensitive populations of passerine birds, but little information is available in the literature concerning the relative effectiveness of different types of cowbird traps or the effects of these traps on non‐target species. We used portable traps to capture cowbirds in 2003–2007 at 3 study areas in southern Nevada and western Arizona. We compared the effectiveness of traps with flat tops versus funnel‐shaped tops in 2005 and compared entrance slots of 2 different widths in 2006–2007. Traps with funnel‐shaped tops had higher cowbird capture rates and lower escape rates than did flat‐topped traps. Funnel‐topped traps also had a higher capture rate of non‐target species. Funnel‐topped traps with a 3.8‐cm‐wide entrance slot had a higher capture rate for male cowbirds than did identical traps with a 3.2‐cm‐wide entrance slot. Capture rates for female cowbirds did not differ between slot sizes, nor did escape rates for either males or females. Capture rates for non‐target species did not differ between slot widths, but wider slots captured larger bodied species (e.g., white‐winged dove [Zenaida asiatica] and great‐tailed grackle [Quiscalus mexicanus]) that were not seen in the traps with narrower slots in the years when both slot widths were tested. Cowbird traps with a funnel‐topped design should be used to maximize the number of cowbirds captured and removed from a site. A slot width of 3.2 cm may minimize non‐target captures, particularly of larger bodied species, while still allowing effective removal of female cowbirds. © 2014 The Wildlife Society.